2014
DOI: 10.1016/j.jocrd.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of relapse following treatment of trichotillomania

Abstract: Objective This study sought to identify predictors of relapse in a behavior therapy trial for trichotillomania (TTM), or hair-pulling disorder. Relapse is common after treatment for TTM, and only a few studies have examined what might predict relapse. Method Data was examined from a TTM treatment study with a stepped-care approach (step 1. web-based self-help; step 2. individual behavior therapy) (N = 60). Implications of significant predictive relations were illustrated by constructing Probability of Treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 48 publications
3
13
0
Order By: Relevance
“…In support of the hypothesis, the dimensional method used in the present study was able to differentiate some patients with different degrees of residual TTM, and, importantly, allowed for prediction of a modest percentage of variance in relapse status 6 months later. Our results could be seen as consistent with that of Falkenstein et al [23], who showed that abstinence from pulling but not urges at post-treatment predicted long-term maintenance of gains. Criterion A1 was found to have the highest difficulty parameter and a high discrimination parameter, meaning that it contributes largely to higher trait parameters and that failure to meet this criterion would signify lower trait levels and make that individual less likely to relapse.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In support of the hypothesis, the dimensional method used in the present study was able to differentiate some patients with different degrees of residual TTM, and, importantly, allowed for prediction of a modest percentage of variance in relapse status 6 months later. Our results could be seen as consistent with that of Falkenstein et al [23], who showed that abstinence from pulling but not urges at post-treatment predicted long-term maintenance of gains. Criterion A1 was found to have the highest difficulty parameter and a high discrimination parameter, meaning that it contributes largely to higher trait parameters and that failure to meet this criterion would signify lower trait levels and make that individual less likely to relapse.…”
Section: Discussionsupporting
confidence: 92%
“…The categorical measurement system fails to capture this essential variability in treatment response. Indeed, one study found that persons with TTM who no longer were pulling hair at the conclusion of treatment were more likely to show long-term maintenance of gains, whereas the residual presence of urges to pull did not predict relapse potential [23]. These results could be seen as applicable to DSM-IV-TR criteria A and B, but that study failed to measure the effect of various endorsement patterns of pulling, urges, and other relevant symptoms on relapse.…”
Section: Introductionmentioning
confidence: 99%
“…One‐week post‐retreat TTM symptom reductions were of similar magnitude to more conventional psychological treatments of longer duration (e.g., Moritz & Rufer, ; Woods et al, ). However, like the findings associated with such conventional treatment, gains from the retreat were not maintained long‐term at the 6‐month or 1‐year follow‐up (Falkenstein et al, ). According to participants, the factors most strongly associated with immediate symptom improvement were at a group level: the sharing of lived experiences, community connection, normalisation, feelings of safely and motivation.…”
Section: Discussionmentioning
confidence: 91%
“…Quantitative measures of TTM symptoms in the current study are comparable to those found in more rigorous treatment trials that have demonstrated decreases in symptom severity post‐treatment, see Supplementary Material Table 3S, for a summary (Diefenbach et al, ; Keuthen et al, ; Moritz & Rufer, ; van Minnen, Hoogduin, Keijsers, Hellenbrand, & Hendriks, ; Woods et al, ). CBT does have some effect on reducing symptoms long term (Falkenstein et al, ), however, the 3‐day retreat did not demonstrate this same effect. Future treatment trials will need to account for the usefulness retreat programs have in reducing hair pulling symptoms by excluding participation in retreats during treatment trials.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation